Mother Tongue Interference Toward Students' Ability In Producing English Sounds - Arafiq; Faradila, Qoonitah; Thohir, Lalu; Amin, Muhammad (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2024)
This study aimed at investigating how students’ mother tongue interferes their pronunciation of English sound and the factors that cause the interference. The research used descriptive qualitative method. The participants of the study were 8th and 9th students of an Islamic junior high school Mataram. Those students are from different families with different local languages comprising Sasak, Sumbawa, and Bima language. The data were collected through pronunciation test, observation sheet and interview guides. The data analysis consisted of data reduction, data display, and conclusion drawing or verification. The findings showed that, two Sasak students struggle to pronounce the consonants voiceless fricative labiodental sound /f/, and the voiced labiodental fricative sound /v/, often substituting them with the voiceless bilabial stop sound /p/. Two Sumbawa students evidently make similar interference to Sasak students, and also struggle to pronounce the vowels open middle central vowel /ə/ and the half-open middle central-tensed vowel /з:/ as the middle front vowel /e/ and close front vowel /i/. One Bimanese student mispronounces the voiced alveolar plosive sound /d/, the voiceless alveolar plosive sound /t/ as the voiced labiodental plosive sound /D/, the voiceless labiodental plosive sound /T/ and three students are struggle to pronounce the vowel sound, similar interference to Sumbawa students. Further, there are six factors that cause interference in students’ pronunciation of English sounds. They are: the use of more than one language, insufficient learning period to train in English sounds, producing English sound using their speaking habits, lack of interest in English, lack of practice, lack of focus in pronunciation during classroom instruction.